Pharmacokinetic equivalence study of nonsteroidal anti-inflammatory drug etoricoxib - Tjandrawinata RR; Setiawati A; Nofiarny D; Susanto LW; Setiawati E (Dove Medical Press, 2018)
Raymond R Tjandrawinata,1 Arini Setiawati,2 Dwi Nofiarny,1 Liana W Susanto,1 Effi Setiawati3 1Dexa Laboratories of Biomolecular Sciences Unit, Dexa Medica Group, Cikarang, West Java, Indonesia; 2Department of Pharmacology and Therapeutics, Medical Faculty, University of Indonesia, Jakarta, Indonesia; 3Bioavailability and Bioequivalence Laboratory Unit, PT Equilab International, Jakarta, Indonesia Purpose: The current study aimed to evaluate whether a generic product of etoricoxib 120 mg film-coated tablet (the test drug) was bioequivalent to the reference product (Arcoxia® film-coated tablet 120 mg).Methods: This was a randomized, open-label, two-sequence, crossover study under fasting condition, with a 14-day washout period, involving 26 healthy adult male and female subjects. Blood samples were taken and analyzed for plasma concentrations of etoricoxib (Chemical Abstracts Service [CAS] 202409-33-4) using a high-pressure liquid chromatography–ultraviolet detector (HPLC-UV) system capable of measuring etoricoxib concentrations ranging from 5.00 to 5002.90 ng/mL, with the lowest limit of quantitation of 5.00 ng/mL. A noncompartmental method was used to determine the pharmacokinetic parameters of a single-dose administration of the drug, including the area under plasma concentration–time curve from time zero to the time of last observed concentration (AUC0-t), the area under plasma concentration–time curve from time zero to infinity (AUC0-∞), the maximum plasma concentration (Cmax), the time to reach the maximum plasma concentration (tmax), and the terminal half-life (t½).Results: After a single-dose administration of etoricoxib 120 mg film-coated tablet, the mean (SD) values for the AUC0-72h and Cmax of the test drug were 45913.42 (13142.19) ng·h/mL and 3155.93 (752.81) ng/mL, respectively; the values for the reference drug were 44577.20 (13541.85) ng⋅h/mL and 2915.13 (772.81) ng/mL, respectively. The geometric mean ratios (90% CIs) of the test drug/reference drug were 103.40% (98.70%–108.32%) for AUC0-72h and 109.26% (100.18%–119.18%) for Cmax. No clinically significant differences in tmax and t½values were found between the test drug and the reference drug. No adverse events were experienced by the subjects during this study.Conclusion: The present study demonstrated that the evaluated generic etoricoxib 120 mg film-coated tablets were bioequivalent to the reference drug. Keywords: bioavailability, bioequivalence, etoricoxib, nonsteroidal anti-inflammatory drug, selective cyclooxygenase-2 inhibitor